Organization design: its evolution within a changing context - Child, John (Henry Stewart Talks, 2010)
Three phases of evolution, Pre-contingency: classical organization theory, scientific management, bureaucracy, human relations, Attention to contingencies: environment, size, charter, technology, personnel, Post-contingency: new organizational forms, Meeting multiple strategic needs, Hybrid organization, Exploitation and exploration, Ambidexterity
Reviewed at 2016/05/31